Biotechnology, justice and health - Faden, R; Powers, M (Oxford Uehiro Centre for Practical Ethics, 2013)
New biotechnologies have the potential to both dramatically improve human well-being and dramatically widen inequalities in well-being. This paper addresses a question that lies squarely on the fault line of these two claims: When as a matter of justice are societies obligated to include a new biotechnology in a national healthcare system? This question is approached from the standpoint of a twin aim theory of justice, in which social structures, including nation-states, have double-barreled theoretical objectives with regard to human well-being. The first aim is to achieve a sufficient level of well-being in each of six core dimensions. In the special case of healthcare systems, this aim is focally but not exclusively attentive to achieving health sufficiency as one of the core dimensions. The second aim is to combat the emergence and persistence of densely woven patterns of systematic disadvantage that tend to undermine the achievement of a sufficient level of health and the other core elements of well-being of some persons and groups. Judgments about entitlements to health related resources, including new biotechnologies, are made in light of a threshold notion of health sufficiency. What is enough or sufficient health? The answer that is defended here is that sufficient health is enough health for a decent human life, understood as enough health to live a full life course without preventable, significant functional disability or decrement in health, or treatable pain or suffering. When a state must include a new biotechnology in its national healthcare system is also influenced by ancillary concerns about the connection between health and other core dimensions of well-being. What counts as a significant functional impairment or health decrement is thus explicated, in part, in relation to the theory’s sufficiency aim for the other essential dimensions of well-being, and thus for a decent life, overall. Those elements of health that play a critical role in the experience of sufficient reasoning, affiliation, security, respect and self determination are especially important; any loss of health function or capacity that threatens the individual’s prospects for sufficiency in these other dimensions, including the relational egalitiarian concerns they entail, constitutes a significant functional impairment. Within national borders, individuals are thus entitled to those health-related goods and services that are essential for a sufficiency of each of the dimensions of well-being; with regard to self determination and respect, what is sufficient by way of guaranteed access to specific goods and services is going to depend on the implications of such access for where an individual stands in relation to her co-nationals. The content of any entitlement to health-related goods and services is also necessarily dynamic. What can be done for health and the other core dimensions of well-being as a function of technological innovation and diffusion is in constant flux. The paper concludes by considering the implications of this analysis for the conditions under which states are obligated to include access in their healthcare systems to one biotechnology, deep brain stimulation.